CRITICAL REVIEW OF ROLE OF POSITRON EMISSION TOMOGRAPHY WITH COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF CANCER THYROID - 1Fahad Khalid Mohammed Dous, 2Emad Rashed Murshed Alrehaili, 3Bandar Abdullah Alluhaybi, 4Fahad Ayed Mohammed Alghtani, 5Hassan Ayed Mohammed Alghtani, 6Abdulrahman Khalil Almughathawi, 7Omar Ali A Alharbi (Chelonian Research Foundation, 2023)
Positron Emission Tomography with Computed Tomography (PET/CT) has emerged as a valuable tool in the diagnosis and management of thyroid cancer. In this survey, the role of PET/CT in cancer conclusion is assessed, counting its benefits, impediments, and prospects. This writing survey investigates various studies and applications to determine the precision of PET/CT in breast cancer. Strategies, comedies, and discoveries (counting figures, tables, and charts) were analyzed and synthesized. The discourse incorporates the preferences and drawbacks of PET/CT, its suggestions for clinical decision-making, and future headings. The findings of this audit emphasize the significance of PET/CT in cancer conclusions and give suggestions for its clinical use. Keywords: Positron Emission Tomography, Computed Tomography, Thyroid Cancer, Diagnosis, PET/CT, Imaging.